2010
DOI: 10.1111/j.1471-4159.2010.07064.x
|View full text |Cite
|
Sign up to set email alerts
|

The deletion of the microtubule‐associated STOP protein affects the serotonergic mouse brain network

Abstract: J. Neurochem. (2010) 115, 1579–1594. Abstract The deletion of microtubule‐associated protein stable tubule only polypeptide (STOP) leads to neuroanatomical, biochemical and severe behavioral alterations in mice, partly alleviated by antipsychotics. Therefore, STOP knockout (KO) mice have been proposed as a model of some schizophrenia‐like symptoms. Preliminary data showed decreased brain serotonin (5‐HT) tissue levels in STOP KO mice. As literature data demonstrate various interactions between microtubule‐asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 67 publications
(89 reference statements)
6
46
0
Order By: Relevance
“…However, further studies are required to elucidate the impact of MAP4343 on neuronal function and structure in vivo, even we report here that MAP4343 appears to exert more rapid and persistent efficacy compared with currently used antidepressant drugs. Additionally, it has been recently suggested that a functional link may exist between microtubule dynamics and central serotonin neurotransmission (27). Interestingly, MAP4343 was found to increase swimming (serotonergic dependent) but not climbing (noradrenergic dependent) behavior in the FST.…”
Section: Discussionmentioning
confidence: 97%
“…However, further studies are required to elucidate the impact of MAP4343 on neuronal function and structure in vivo, even we report here that MAP4343 appears to exert more rapid and persistent efficacy compared with currently used antidepressant drugs. Additionally, it has been recently suggested that a functional link may exist between microtubule dynamics and central serotonin neurotransmission (27). Interestingly, MAP4343 was found to increase swimming (serotonergic dependent) but not climbing (noradrenergic dependent) behavior in the FST.…”
Section: Discussionmentioning
confidence: 97%
“…The two main isoforms of MAP6 MAP6-E, which is expressed during neurodevelopment and in the adult brain, and MAP6-N, which is expressed postnatally1625, exhibit pronounced axonal localization2627. MAP6 null mice (MAP6 KO) are viable but display severe behavioural disorders associated with synaptic plasticity impairments and exhibit alterations in multiple neurotransmission23282930. Their behavioural and biological alterations resemble schizophrenia-related symptoms, and indeed, long-term treatment with antipsychotic drugs alleviates several of the behavioural and biological defects233132.…”
mentioning
confidence: 99%
“…Their behavioural and biological alterations resemble schizophrenia-related symptoms, and indeed, long-term treatment with antipsychotic drugs alleviates several of the behavioural and biological defects233132. Their behavioural impairments may also rely on axonal disconnectivity, as some evidence points to structural changes in brain anatomy and connectivity of MAP6-KO mice26283334. However, a global and detailed analysis of brain alterations is as yet missing.…”
mentioning
confidence: 99%
“…Depleted synaptic vesicle pool Andrieux et al (2002), Brun et al (2005), Bouvrais-Veret et al (2007), (2008), Powell et al (2007), Fradley et al (2005), Fournet et al (2010Fournet et al ( , (2012b, and Daoust et al (2014) Impaired synaptic plasticity Severe behavioral disorders Abnormalities of glutamatergic, dopaminergic, acetylcholinergic/nicotinic, serotonergic, and noradrenergic neurotransmissions Sensorimotor gating impairment Defects in neuronal transport MAP7 Viable. Defects in spermatogenesis Komada et al (2000), Sung et al (2008), Barlan et al (2013), and Metzger et al (2012) Reduced viability (in Drosophila) Myonuclear positioning altered (in Drosophila)…”
Section: Map6mentioning
confidence: 99%
“…Initial studies showed that MAP6 knockout mice have reduced number of synaptic vesicles and impaired synaptic plasticity (Andrieux et al 2002). Later, it was shown that, in addition to changes in glutamatergic synaptic transmission, these mice also present alterations in dopaminergic, acetylcholinergic, nicotinic, serotonergic, and noradrenergic neurotransmission (Bouvrais-Veret et al 2007, 2008Brun et al 2005;Delotterie et al 2010;Fournet et al 2010Fournet et al , 2012bFradley et al 2005;Kajitani et al 2010;Powell et al 2007). These alterations recapitulate some clinical features observed in schizophrenia disorders (Andrieux et al 2002;Fournet et al 2012b).…”
Section: Map6 Family Of Microtubule-associated Proteinsmentioning
confidence: 99%